Doszklistkowe iniekcje ranibizumabu w leczeniu cukrzycowego obrzęku plamki - Kubicka-Trząska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Anti-vascular endothelial growth factor (anti-VEGF) therapies that inhibit choroidal angiogenesis and reduce vascular permeability have revolutionized clinical practices for neovascular eye diseases. Ranibizumab (Lucentis) is a Fab-antibody with high affinity for VEGF, and has a potential to bind to all VEGF isoforms. Diseases of retinal and choroidal vasculature are the most prevalent causes of vision loss in developed countries. Among them diabetic macular edema (DME) is the most common sight threatening complication of diabetes. VEGF plays a critical role in the pathogenesis of DME. Due to modest outcomes with macular photocoagulation, other treatment modalities for DME have been evaluated. The results of the pilot studies and preliminary results of multicenter randomized, controlled studies showed that intraocular injections of ranibizumab decrease the mean retinal thickness and improve the BCVA (best corrected visual acuity) in patients with DME.